Differential pulmonary immunopathology of domestic sheep (Ovis aries) and bighorn sheep (Ovis canadensis) with Mycoplasma ovipneumoniae infection: A retrospective study. (June 2021) - Grossman, Paige C.; Schneider, David A.; Herndon, David R.; Knowles, Donald P.; Highland, Margaret A.
Highlights: Lung IL-17 increased in BHS and decreased in DS with M. ovipneumoniae infection. Greater increase in bronchiolar CD3 with M. ovipneumoniae infection in BHS than DS. Greater increase in CD20 and CD79a with M. ovipneumoniae infection in DS than BHS. M. ovipneumoniae infection is associated with increased lung CD163 in BHS, not in DS. Abstract: Mycoplasma ovipneumoniae is a respiratory pathogen that impacts domestic sheep ( Ovis aries ; DS ) and bighorn sheep ( Ovis canadensis ; BHS). BHS are reported to be more susceptible than DS to developing polymicrobial pneumonia associated with M. ovipneumoniae infection. Using formalin-fixed paraffin-embedded tissues, we performed a retrospective study investigating the pulmonary immune response of DS and BHS to M. ovipneumoniae infection. M. ovipneumoniae infected DS exhibited a more robust and well-organized BALT formation as compared to BHS. Digital analysis of immunohistochemical chromogen deposition in lung tissue was used to quantitate T cell marker CD3, B cell markers CD20 and CD79a, macrophage markers CD163 and Iba1, and cytokine IL-17. A significant interaction of species and infection status was identified for CD3, CD163, and IL-17. BHS had a greater increase in bronchiolar CD3 and bronchiolar and alveolar CD163 with infection, as compared to DS. BHS had an increase in bronchiolar associated lymph tissue (BALT) and alveolar IL-17 with infection, while these remained similar in DS regardless of infection status. IL-17 in respiratory epithelium of bronchi and bronchioles comparatively decreased in DS and increased in BHS with infection. These data begin to define the interspecies differential immune response to pulmonary M. ovipneumoniae infection in DS and BHS and provide the first investigations of respiratory epithelium-associated IL-17 in ovine.